IMPLEMENTASI TERAPI KELOMPOK TERAPEUTIK DALAM MENGOPTIMALKAN PERAN DAN FUNGSI SUAMI-ISTRI DALAM MENINGKATKAN PRODUKTIVITAS PERTANIAN DI KABUPATEN HUMBANG HASUNDUTAN - Wahyuni, Sri Eka; Daulay, Wardiyah; Purba, Jenny Marlindawany; Nasution, Mahnum Lailan (Jurnal Abdimas Mutiara, 2022)
Humbang Hasundutan is one of the districts in North Sumatra Province. The majority of people in Humbang Hasundutan Regency are Batak and work in the agricultural sector, especially food crop farming, namely lowland rice, lowland rice, corn, peanuts, cassava, sweet potato, pelawija, horticulture, and smallholder plantations. From the results of interviews with the people of Humbang Hasundutan Regency, the role and function of the husband in managing agricultural land is still lacking. It is customary for Batak men in Humbang Hasundutan to meet, relax, and tell stories at the tuak lapo. The purpose of this community service is to provide education through therapeutic group therapy to increase the productivity of high agricultural products. The roles and functions of husband and wife were measured using a measuring instrument, namely the Developmental Tasks on Adult Questionnaire-10 instrument. This instrument identifies adult developmental problems experienced by respondents. From the results of the questionnaire, it was found that the majority of respondents have not been able to meet adult development, which is indicated by the community not having new innovations and preferring to stay in the jobs they like. Through therapeutic group therapy, it is expected to increase the ability of husband and wife roles and functions in terms of increasing agricultural productivity in Ria Ria Village, Pollung District, Humbang Hasundutan Regency.